1988
DOI: 10.1093/carcin/9.6.959
|View full text |Cite
|
Sign up to set email alerts
|

Examination of genotoxicity, toxicity and morphologic alterations in hepatocytes following in vivo or in vitro exposure to methapyrilene

Abstract: The antihistamine methapyrilene (MP) was widely used as a component of cold, allergy and sleep-aid medications in the 1970s until it was identified as a potent rat liver carcinogen. MP does not induce positive responses in most short-term genotoxicity assays, which suggests that it is carcinogenic by a non-genotoxic mechanism. We have evaluated the potential of MP to induce unscheduled DNA synthesis (UDS), a genetic end point and S-phase synthesis (SPS), and indicator of cell proliferation, in Fischer-344 (F34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 0 publications
3
15
0
Order By: Relevance
“…Acute gavage of 225 mg/kg MP caused hepatic necrosis, increased mitotic figures, and elevated serum enzyme levels characteristic of hepatotoxicity (Lijinsky et al 1980). In a 3-day oral gavage study, 150 mg/kg/day MP resulted in periportal hepatic damage (Steinmetz et al 1988). Previous results also showed that 50 mg/kg/day during 3 days resulted in Environmental Health Perspectives • VOLUME 112 | NUMBER 4 | March 2004…”
Section: Methodsmentioning
confidence: 95%
“…Acute gavage of 225 mg/kg MP caused hepatic necrosis, increased mitotic figures, and elevated serum enzyme levels characteristic of hepatotoxicity (Lijinsky et al 1980). In a 3-day oral gavage study, 150 mg/kg/day MP resulted in periportal hepatic damage (Steinmetz et al 1988). Previous results also showed that 50 mg/kg/day during 3 days resulted in Environmental Health Perspectives • VOLUME 112 | NUMBER 4 | March 2004…”
Section: Methodsmentioning
confidence: 95%
“…Neither WY-14643 nor DEHP produced hyperplasia at the site of skin application in the Tg.AC studies. Methapyrilene is also an hepatocarcinogen but its carcinogenicity is secondary to hepatocyte toxicity and regenerative hyperplasia (30), suggesting that methapyrilene-induced proliferation may be limited The site of application was the shaved dorsal skin in the topical studies and the forestomach in the gavage studies. 2 For the topical studies, chemical CYC was applied in ethanol/water (1:1)…”
Section: Discussionmentioning
confidence: 99%
“…It is now considered to be a rat-specific carcinogen since hepatocellular carcinoma and cholangiocarcinoma were induced by administration of MP at 1000 ppm for 64 weeks, whereas no such findings were observed either in Syrian hamsters, Guinea-pigs, B6C3F1 mice, or humans (Mirsalis, 1987). As for its genotoxicity, the Ames test, DNA addition test, chromosome abnormality test (NTP, 2000) and irregular DNA synthesis test in rat and mouse (Steinmetz et al, 1988) were all negative, whereas the cell transformation assay and L5178Y/TK+/− mouse lymphoma assay were positive (Turner et al, 1987). Based on these observations, hepatocarcinogenicity of MP in rat has been considered to be non-genotoxic, whereas the involvement of its initiation activity cannot be completely excluded (Althaus et al, …”
Section: Discussionmentioning
confidence: 99%